Terrorist transgressions: Exploring the gendered representations of the terrorist - Malvern, Sue; Koureas, Gabriel (My University, 2014)
The primary aim of the Terrorist Transgressions network which is presented here was to analyse the myths inscribed in images of the terrorist and identify how agency is attributed to representation through invocations and inversions of gender stereotypes. Although terrorism, its contexts, histories and forms, has been the focus of intense academic activity in recent years, especially in the fields of politics and international relations, cultural representations of the terrorist have received less attention. While the terrorist is predominantly aligned with masculinity, women have been active in terrorist organizations since the late nineteenth century. Particularly since the 1980s, women have perpetrated suicidal terrorist attacks, including suicide bombing, where the body becomes a weapon. Such attacks have confounded constructions of femininity and masculinity, with profound implications for the gendering of violence and horror. The network established that there is a shift away from analyses of cultural representations of the Red Army Faction, which have dominated the literature since the 1980s. New work has emerged examining representations of the terrorist and gender, including investigations of material from the 1970s, recently made available in archives. There also has been a shift in terms of military discourses around the figure of the enemy or terrorist insurgent in relation to visualizing the invisible enemy. Emerging work on colonial insurgencies contributed to a historical understanding of such debates.
Keywords: Terrorist; Visuality; Feminism; Masculinity; Gender